In vitro antibacterial activity of imipenem in combination with colistin against multidrug-resistant Pseudomonas aeruginosa - Sirinat Phanuwong (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2007